Among the Impostors - Haddix, Margaret Peterson (New York Simon & Schuster Books for Young Readers, 2001)
In a future where the law limits a family to only two children, third-born Luke has been in hiding for the entire twelve years of his life, until he enters boarding school under an assumed name and is forced to face his fears.
Sequel to: Among the hidden.
620L
81946
Keywords: Fear -- Fiction; Interpersonal relations -- Fiction; Science fiction